Synthesis, characterization, and cytotoxicity of binuclear copper(II) complexes with tetradentate nitrogen-containing ligands bis-5-(2-pyridylmethylidene)-3, 5-dihydro-4H-imidazol-4-ones. (1st July 2018) - Beloglazkina, Elena K.; Krasnovskaya, Olga O.; Guk, Dmitry A.; Tafeenko, Viktor A.; Moiseeva, Anna A.; Zyk, Nikolai V.; Majouga, Alexander G.
Graphical abstract: Binuclear copper(II) complexes of bis-5-(2-pyridylmethylidene)-3, 5-dihydro-4 H -imidazol-4-ones with distorted tetrahedral environment of copper atoms and Cu–Cu distances about 4.6 Å were synthesized. Abstract: A treatment of the N4 -type organic ligands containing two 5-(2-pyridylmethylidene)-2-thio-3, 5-dihydro-4 H -imidazol-4-one fragments linked by (CH2 )2 bridges between the sulfur atoms with CuCl2 affords to binuclear copper(II) complexes of corresponding ligands. A series of copper complexes with L(CuCl2 )2 composition were isolated and characterized by elemental analysis, UV–Vis spectra and cyclic voltammetry; the X-ray crystal structures of four synthesized complexes showed the distorted tetrahedral environment of both copper atoms; Cu–Cu distances is about 4.5 Å, which is confirming the absence of interaction between copper ions. Electrochemical studies of complexes demonstrated the simultaneous reduction of each of the coordinated copper atoms at a potential of +0.39 to +0.43 V.